2019
DOI: 10.3389/fchem.2019.00091
|View full text |Cite
|
Sign up to set email alerts
|

Ag Loading Enhanced Photocatalytic Activity of g-C3N4 Porous Nanosheets for Decomposition of Organic Pollutants

Abstract: The g-C 3 N 4 porous nanosheets with different loading amount of Ag nanoparticles (NPs) are successfully prepared by a simple liquid-phase reduction method. These Ag/g-C 3 N 4 composites have an improved photocatalytic performance for decomposing organic pollutants compared with that of pure g-C 3 N 4 nanosheets. Many measurements have been used for characterizing the sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(37 citation statements)
references
References 57 publications
7
30
0
Order By: Relevance
“…Notably, the PL intensity of the Cu 7 S 4 sample with nanotwinned structure decreases significantly compared with that of sample without nanotwinned building blocks, suggesting a slower recombination rate of photoinduced electrons and holes in sample with nanotwinned building blocks. The similar results are also reported in multiple literatures, for example, Shen et al (2015), Qi et al (2019) etc. The photodegradation and electrochemical impedance spectra of samples also confirm the above results (Figures 7A,B).…”
Section: Photoluminescence Spectrasupporting
confidence: 90%
“…Notably, the PL intensity of the Cu 7 S 4 sample with nanotwinned structure decreases significantly compared with that of sample without nanotwinned building blocks, suggesting a slower recombination rate of photoinduced electrons and holes in sample with nanotwinned building blocks. The similar results are also reported in multiple literatures, for example, Shen et al (2015), Qi et al (2019) etc. The photodegradation and electrochemical impedance spectra of samples also confirm the above results (Figures 7A,B).…”
Section: Photoluminescence Spectrasupporting
confidence: 90%
“…Powder X-ray diffraction (XRD) pattern of the fabricated BZnO and FZnO nanoparticles are recorded by Philips X-ray Diffractrometer (X' Pert Pro) with Cu K α1 radiation (λ = 1.5406 Å). Field Effect Scanning Electron Microscope (MIRA3 TESCAN) and Transmission Electron Microscope (JEM-2100, Jeol) were used for confirmation of FZnO microstructures 20 . The optical absorption spectra of ZnO dispersed in methylene blue (MB) dye are recorded by a UV-vis spectrophotometer (HITACHI U -3210).…”
Section: Methodsmentioning
confidence: 99%
“…Besides, capping agent PVP tends to adsorb on the {10-10} planes of the six symmetric side facets of the growth nuclei, thereby it allows to occur only along the polar axis 14,20,21 .…”
Section: +mentioning
confidence: 99%
“…Studies based on g-C 3 N 4 have been mostly carried out in attempt to reduce the recombination rate of photogenerated electron-hole pairs, in addition to reduce the energy band gap. Effective procedures may be referred to as—(i) creating heterojunctions like semiconductor-semiconductor [ 29 , 30 , 31 ] or metal-semiconductor [ 32 , 33 , 34 ] in order to effectively separate electrons and holes; (ii) doping metallic elements into g-C 3 N 4 as electron trapping centers [ 35 , 36 ], leaving highly oxidized holes. Recent works showed that the incorporation of metal ions into g-C 3 N 4 polymerization network not only improves charge carrier lifetime and mobilities but also reduces the band gap of g-C 3 N 4 .…”
Section: Introductionmentioning
confidence: 99%